The improved empirical and naturalistic methods for forecasting methane content in the coal seams - Sheiko, A.V. (Геотехнічна механіка, 2018)
The research is related to the field of the mine gas safety and assessment of methane reserves in the methane-coal deposits. A scope of literature and stock data were summarized, and empirical methods for determining methane content in coalbeds were improved (statistical geological, mining statistical and semi empirical methods). Impact of tectonic structures of coal deposits on the methane relative content was determined. Pattern of depth effect on methane content in the coal seams was established. The mining statistical method for forecasting gas emissions was improved by taking into considerartion effect of depth, rock inclination, seam thickness and methods for controlling rock pressure on the gas emissions from the coal seam. The quantitative estimation of methane share emitted from the mine rocks in the total gas balance of the mining site was done. The semi-empirical method for predicting methane content in coal seams was improved by taking into account the Hilt-Skok’s law and the established patterns of the effect of unloading, depth and strength of rocks on thermobaric conditions, which predefine gas content in the coal seams. The research results were implemented in the projects of Dneprogiproshakht Institute. The evidence-based part of the improved methods were presentred in different scientific reports of the N.Poljakov Institute of Geotechnical Mechanics of the National Academy of Sciences of Ukraine and Dniprogiproshakht Institute.